The Implementation of the WhatsApp Blast Strategy in Optimizing the BTH University Dormitory as a Student Behaviour Based Digital Marketing Communication Model - Maria, Hana Diana; Kusumah, Firdan Gusmara; Pamungkas, Adie; Cahya, Azwan; Nata, Septiawan Dwi; Saputeri, Trisha Andini; Shahida, Sopa Marwah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Siliwangi, 2025)
This study aims to analyze the implementation of WhatsApp Blast strategy in supporting the optimization of dormitory services at Universitas Bakti Tunas Husada as a digital marketing communication model based on student behavior. The research employs a quantitative approach with an explanatory design. Data were collected through a structured questionnaire distributed to 121 students residing at BTH Student House.The independent variables in this study consist of WhatsApp Blast strategy, dormitory optimization, and digital marketing model, while student behavior is positioned as the dependent variable. Data analysis was conducted using multiple linear regression with SPSS software. The results indicate that the WhatsApp Blast strategy plays an important role in shaping students’ responses to institutional information, particularly in terms of attention, understanding, and behavioral tendencies. Dormitory optimization strengthens the effectiveness of digital communication by providing service support that is directly experienced by students. Meanwhile, the digital marketing model functions as an integrative framework that aligns communication messages with service implementation.Simultaneously, all independent variables contribute to the formation of student behavior within the dormitory environment. This study highlights the importance of integrating digital communication strategies with service quality in managing internal communication in higher education institutions. Based on the simultaneous test results, the implementation of a student behavior–based WhatsApp Blast strategy has a significant effect on optimizing the BTH University Dormitory as a digital marketing communication model. This is evidenced by an F-value of 138.412 with a significance level of 0.000, indicating a statistically robust research model. The coefficient of determination (R²) of 0.376 suggests that 81,7% of dormitory optimization is explained by the WhatsApp Blast strategy, while the remaining 18.3% is influenced by other factors beyond this study.